1997
DOI: 10.1080/15216549700204821
|View full text |Cite
|
Sign up to set email alerts
|

The irradiation of hepatocytes with He‐Ne laser causes an increase of cytosolic free calcium concentration and an increase of cell membrane potential, correlated with it, both increases taking place in an oscillatory manner

Abstract: Isolated hepatocytes were irradiated with Helium‐Neon laser (fluence: 0.24 Joules x cm‐2, fluence rate: 12 mW x cm‐2 and changes of both cytosolic free Ca2+ concentration and cell membrane potential were checked by measuring fura‐2 and bis‐oxonol fluorescence respectively. Irradiation resulted in an enhancement in cytosolic free Ca2+ concentration that requires the presence of Ca2+ in the phase outside hepatocytes; consistently an increase in cell membrane potential was measured correlated with it. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 8 publications
1
15
0
2
Order By: Relevance
“…Two circumstances considering complex changes in the mitochondrial characteristics of retrograde signaling should be underlined. First, there exists a unique mitochondrial oscillator that depends on oxidative phosphorylation, ROS and permeability of mitochondrial inner membrane ion channels (61,62). It was hypothesized that the balance between O 2 •− efflux through inner membrane anion channels and the intracellular ROS scavenging capacity plays a key role in the oscillation mechanism.…”
Section: Ros Signalingmentioning
confidence: 99%
“…Two circumstances considering complex changes in the mitochondrial characteristics of retrograde signaling should be underlined. First, there exists a unique mitochondrial oscillator that depends on oxidative phosphorylation, ROS and permeability of mitochondrial inner membrane ion channels (61,62). It was hypothesized that the balance between O 2 •− efflux through inner membrane anion channels and the intracellular ROS scavenging capacity plays a key role in the oscillation mechanism.…”
Section: Ros Signalingmentioning
confidence: 99%
“…Laser irradiation has been shown to induce changes in intracellular Ca 2+ concentrations in macrophages, hepatocytes [17], and osteoblasts [18] in vitro. In this study, we first demonstrated an immediate increase in intracellular calcium levels 15 and 30 min after 1 J/ cm 2 laser stimulation in tenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…correspondientes a hepatocitos de rata estimuladas con dosis crecientes de láser infrarrojo. En este contexto, nuestros resultados son disímiles en cuanto a la energía utilizada puesto que Greco et al (1996Greco et al ( , 2001) y Vacca et al (1997) utilizan 0.24 J/ cm 2 como energía activadora sobre hepatocitos probando grandes modificaciones de la función celular producto de dicha estimulación.…”
Section: Discussionunclassified
“…Así, Vacca et al (1993) comprueban activación en la replicación de DNA mitocondrial; Cieslar et al (1995) determinaron un notable incremento en las actividades enzimá-ticas tanto de membranas plasmáticas como mitocondriales. Vacca et al (1997) comunicaron que la irradiaciones infrarrojas generan aumentos considerables del calcio citoplasmático libre en relación con el potencial de membrana plasmática; del mismo modo, Greco et al (2001) precisaron que la estimulación con esta energía produce incremento en la concentración de calcio mitocondrial generando de este modo una hiperpolarización de membrana del organelo generador de energía.…”
Section: Discussionunclassified